PENGARUH LAMA PENYIMPANAN TERHADAP KADAR AIR, ABU DAN BAHAN ORGANIK WAFER PAKAN KOMPLIT JERAMI JAGUNG - Betty Bagau; Sony A E Moningkey; Stevy P Pangemanan (Jambura Journal of Animal Science, 2023)
Corn straw contains dry matter and organic matter which are nutrients that are needed by livestock, but have high crude fiber, low digestibility and protein content, are bulky (voluminous) and are not economical and inefficient to be transported to areas other. One of the technologies that can be used is a complete wafer-shaped feed technology that consists of fiber feed, namely corn straw and concentrate with a composition based on the nutritional needs of livestock, efficient in storage and transportation and ensures availability in the season of feed shortages. Based on this, this research was carried out with the aim of knowing the effect of different storage periods on water content, ash content, and organic matter of corn straw complete feed wafers. The materials used in this study were corn straw, finished feed concentrate, additives/complementary materials. The tools used in this research are: lawn mowers/waste such as sickles and choppers, milling machines, presses, heaters and molds with a size (15 x 15 x 5) cm. Parameters measured were water content, ash content, and organic matter. The results of the analysis of diversity showed that the effect of storage time on complete feed wafers of corn straw had a significantly different effect (P0.05) on moisture content and ash content and organic matter of complete feed wafers. Further test Honest Significant Difference on water content and ash content of P0 treatment had no significant effect (P 0.05) with P1; but significantly different (P0.05) higher with P2 and P3, while P2 had the same effect as P3. BNJ test for organic matter treatment P0 was significantly different (P0.05) with P1; P2 and P3; Likewise, P1 was significantly different (P0.05) with P2 and P3, while P2 and P3 were not significantly different (P0.05). Based on the results of this study, it can be concluded that complete feed wafers based on corn straw can be stored for up to 6 weeks, based on moisture content, ash content and organic matter.